Lack of association between clinical and ultrasound measures of disease activity in rheumatoid arthritis remission. (May 2020) - Baker, Kenneth F.; Thompson, Ben; Lendrem, Dennis W.; Scadeng, Adam; Pratt, Arthur G.; Isaacs, John D.
Objectives: The objective of this study was to assess the prevalence of ultrasound (US) abnormalities and association with clinical parameters in rheumatoid arthritis (RA) clinical remission. Methods: Patients with established RA in clinical remission (DAS28-CRP < 2.4) taking conventional synthetic disease-modifying anti-rheumatic drugs were recruited as part of the Biomarkers of Remission in Rheumatoid Arthritis (BioRRA) Study. In addition, patients from the Newcastle Early Arthritis Clinic (NEAC) with early active RA (DAS28-CRP > 2.4) or seronegative non-inflammatory arthralgia (NIA) were studied as positive and negative controls, respectively. The association between individual dependent variables (synovial power Doppler and greyscale, tenosynovial greyscale, and erosions) and clinical parameters was assessed by multivariate ordinal logistic regression, with adjustment for multiple testing. Results: A total of 294 patients were included: 66 RA in remission, 146 active RA, and 82 NIA. Within the active RA group, significant associations were observed between swollen joint count and higher total synovial greyscale score (OR 1.17 95% CI 1.08–1.26, p < 0.001) and higher total synovial power Doppler score (OR 1.20, 95% CI 1.12–1.30, p < 0.001). No significant associations were observed for the NIA group. In the RA remission group, US abnormalities were frequently observed and comparable for both DAS28-CRP and 2011 ACR/EULAR Boolean remission, with no significant association with clinical parameters identified. Conclusion: We observed widespread subclinical US findings in RA patients in clinical remission, even when remission is defined using the stringent ACR/EULAR Boolean criteria. In contrast to active disease, synovial power Doppler failed to show significant association with any of the clinical parameters in RA remission. Our results suggest that clinical and US examinations are non-overlapping in evaluating RA remission, challenging the proposition of US-driven management strategies in this setting.